(3haGI GdEeGe GdQVGs - (3eLghds ((3CShjgj Hf Tfhas)
(3ChdgG (B:s
(3ceG MHS CHhg ehSi GdcGXe Ydjg GdSdGe, gcPG Mci CHh YHO Gddg LO GdefPQ GHf gTGe GdcdHjs
(3BNQgG (B:s
(3hCNHQhg HeG UGQ efgG eY GdQVG Ydjg GdSdGe, aTgb TgbI heVJ QhMg Edi GdfGQ(B... (3hOafg dYfg Gddg JYGdi, hUdi Gddg Ydi eMeO hBdg(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJGQjNs